2009
DOI: 10.1029/2009jd012352
|View full text |Cite
|
Sign up to set email alerts
|

Dominant role by vertical wind shear in regulating aerosol effects on deep convective clouds

Abstract: [1] Aerosol-cloud interaction is recognized as one of the key factors influencing cloud properties and precipitation regimes across local, regional, and global scales and remains one of the largest uncertainties in understanding and projecting future climate changes. Deep convective clouds (DCCs) play a crucial role in the general circulation, energy balance, and hydrological cycle of our climate system. The complex aerosol-DCC interactions continue to be puzzling as more ''aerosol effects'' unfold, and system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
316
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(363 citation statements)
references
References 60 publications
29
316
1
2
Order By: Relevance
“…Increased IN are thereby depicted to reduce the net cooling impact of such clouds on the planet and vice versa (8). Nevertheless, we must note that the sign and magnitude of the impact remains in question, because cloud modeling studies find that IN increases may lead as well to precipitation decreases, and their impact cannot necessarily be isolated from impacts of increases in all types of aerosols on the warm phase (>0°C) regions of clouds (9), nor the dynamical context in which clouds form (10). The sign and magnitude of the effects of increased IN on high (cirrus) clouds is similarly uncertain, but the impact is likely to be a decrease in the net planetary warming of this cloud type.…”
mentioning
confidence: 99%
“…Increased IN are thereby depicted to reduce the net cooling impact of such clouds on the planet and vice versa (8). Nevertheless, we must note that the sign and magnitude of the impact remains in question, because cloud modeling studies find that IN increases may lead as well to precipitation decreases, and their impact cannot necessarily be isolated from impacts of increases in all types of aerosols on the warm phase (>0°C) regions of clouds (9), nor the dynamical context in which clouds form (10). The sign and magnitude of the effects of increased IN on high (cirrus) clouds is similarly uncertain, but the impact is likely to be a decrease in the net planetary warming of this cloud type.…”
mentioning
confidence: 99%
“…Many environmental parameters, such as the CAPE (18-21), RH (13,20,22,23), and VWS (12,22,26,28,34), have been known to influence MCSs' lifetime. However, to our knowledge, this is the first satellite-based global tropical continental-scale assessment of the relative roles of meteorological conditions versus aerosols in determining the variations of cloud ice and lifetime of the MCSs using collocated geostationary satellites, closely synchronized A-train polar orbital satellite, and MERRA reanalysis datasets on MCSs' lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…For example, model simulation has shown that an increase in aerosol concentrations up to an optimal level can invigorate the MCSs under weak vertical wind shear (VWS) and higher RH but suppress the MCSs under strong VWS in a dry environment (12,13). They found that, due to a significant enhancement in the convective available potential energy (CAPE), corresponding to an increase in RH from 50% to 70%, aerosol impact on ice crystal mass becomes pronounced, with a dramatic increase in the size of the anvils and the mass of ice crystals of the deep convection.…”
mentioning
confidence: 99%
“…In deep convective clouds rain forms eventually, but the aerosol-induced delay in its formation to greater heights was shown to cause in some conditions cloud invigoration (Andreae et al, 2004;Rosenfeld et al, 2008a;Fan et al, 2012) and additional electrification (Yuan et al, 2011). The invigoration was shown to occur mainly for situations with weak wind shear and for clouds with warm base, in which there is large vertical distance between cloud base and the freezing level (Fan et al, 2009;Li et al, 2011). The aerosolinduced vertical growth and the consequent expansion of the anvils into cirrus was observed (Koren et al, 2010) and simulated (Fan et al, 2012) to inflict large positive radiative forcing, in contrast to the strong negative forcing that is caused by the aerosol effect on shallow clouds, at least in heavily drizzling marine stratocumulus (e.g., Albrecht, 1989).…”
Section: Ways By Which Aerosols Affect Cloud Microphysical Precipitamentioning
confidence: 99%